2012
DOI: 10.1136/bjsports-2012-091022
|View full text |Cite
|
Sign up to set email alerts
|

Injury risk in Danish youth and senior elite handball using a new SMS text messages approach

Abstract: The incidence of time-loss injuries in elite handball was higher during match play than previously reported in recreational handball. Previous injuries were a risk factor for new injuries among u-16 players. Male players had a significant higher injury rate in the u-18 group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
169
10
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(213 citation statements)
references
References 32 publications
(20 reference statements)
22
169
10
8
Order By: Relevance
“…In team handball data and recent research state that previous injuries increase the risk for recurring injuries, in particular with regard to injuries of the lower extremities , Myklebust et al, 2013, Moller et al 2012. The findings of the present study however ( Table 2), showed that only 13.2% of male athletes and 13.6% of female athletes had a recurrence to an older injury.…”
Section: Volume 12 | Issue 3 | 2017 | 695contrasting
confidence: 72%
“…In team handball data and recent research state that previous injuries increase the risk for recurring injuries, in particular with regard to injuries of the lower extremities , Myklebust et al, 2013, Moller et al 2012. The findings of the present study however ( Table 2), showed that only 13.2% of male athletes and 13.6% of female athletes had a recurrence to an older injury.…”
Section: Volume 12 | Issue 3 | 2017 | 695contrasting
confidence: 72%
“…The knee, ankle and thigh were the sites with more frequency of injuries in the athletes included in the present study. Similar results were also found in other studies [11][12][13]19 . This may be associated with greater demand and exposure of these joints in contact sports.…”
Section: Discussionsupporting
confidence: 92%
“…However, the number of injury in handball was high in lower limb, following upper limb and trunk. Other studies have also shown the same results in this modality 12,19 . The knee, ankle and thigh were the sites with more frequency of injuries in the athletes included in the present study.…”
Section: Discussionsupporting
confidence: 72%
“…However, comparisons of the results are limited since age is a risk factor of injuries [11,18]. Among other athletes, prevalence of overuse injuries of 31% in handball and 23% in track and field athletes have been reported [19,20]. The participants in these studies were all elite athletes aged 15 years or older, hence a higher prevalence of overuse injuries is expected.…”
Section: Discussionmentioning
confidence: 99%